The Primary School Learners’ Mathematics Communication Skill Improvement through PBL and TGT Models - Melyana Indiarsih; Eko Purwanti; Yuli Kurniawati (Educational Management, 2021)
This research aims to find out the primary school learners’ mathematics communication skills through PBL and TGT models. This research is a quantitative approached research. The research method is a quasi-experimental method with a non-equivalent pre-test and post-test control group design. The technique of collecting data was cluster random sampling. The sample consisted of the fifth graders of Primary School in Jatinangor. The school has applied the 2013 curriculum. The fifth graders of Sinargalih Public Primary School were taken as the experimental group while the fifth graders of Mekarsari Public Primary School were taken as the control group. The data collection were done by distributing the Mathematics Communication Skill Test (MCST), observation sheet, and interview. The applied data analysis was an Independent simple T-test and hypothesis test. The findings showed that there was the learners’ mathematics communication skill improvements taught by PBL or TGT, and the significant improvement the learners taught by PBL. The results obtained an average score of students taught by PBL was higher with 70.23 than TGT with a score of 65.30. It could be concluded there was significant improvement of learners’ mathematics communication skills taught by PBL or TGT models. Keywords: PBL, TGT, Mathematics Communication Skill